Expansion in Nicoby and Vincent Zabus' Graphic Novel Sophie's World: A Comparative Literary Study - Lisa, Lisa Kusuma Aprilia; Eva Eri Dia (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
In this era comics are no longer perceived as a lowbrow art form synonymous with disposable, single-read stories. Comics are now recognized as a vessel or medium that contains ideas and narratives, much like film, novels, and other literary works. Consequently, many literary novels are now being adapted into comics, also termed graphic novels, to broaden the target readership of the original work .This research selects the graphic novel Sophie's World by Nicoby and Vincent Zabus and its original source novel, Sophie's World by Jostein Gaarder, as its primary objects of study. This study aims to describe the expansions found within the graphic novel as a transformational work derived from the original novel. The research data consists of sentences and paragraphs related to the expansions present in the graphic novel. A comparative analysis between the graphic novel and the original novel reveals that the expansions primarily manifest as additions of information and content to the elements of character, setting, and plot. Crucially, although these expansions exist in the graphic novel adaptation, they do not alter or impact the core philosophical concepts conveyed in the original source material.